About polyhedrane “cages” and their doubtful supramolecular lodging capacity: a demonstration by the absurd and a plea for free expression in scientific journals - Riess, Jean G. (Comptes Rendus. Chimie)
Polyhedral “cage” compounds such as cubane, adamantane, dodecahedrane, and their perfluorinated analogs, despite their appellation and standard representation, show little aptitude for supramolecular host–guest chemistry. The mere inspection of covalent and van der Waals atomic radii should convince the most dubious Reader of that. Yet, some perplexing patents claim the insertion of oxygen molecules within perfluorohexamethylenetetramine, a (not yet documented) compound that is structurally related to perfluoroadamantane. The question of the publishability of a skeptical opinion on such techno-legal documents in scientific journals is raised. Further considerations relate to didactic approaches, correction of misconceptions, scientific edition challenges, publication ethics, societal awareness, scientists’ accountability, and include a plea for freedom of expression, increased transparency in the article reviewing process, and enhanced communication between, editors, referees, and authors. The referees’ comments on this opinion paper and author’s responses are provided as supplementary data.